2003
DOI: 10.1093/aje/kwg227
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Household Contacts of Infectious Cases in Kampala, Uganda

Abstract: Tuberculosis remains a serious threat to public health, especially in sub-Saharan Africa. To determine the host and environmental factors responsible for tuberculosis in African households, the authors performed a prospective cohort study of 1,206 household contacts of 302 index cases with tuberculosis enrolled in Uganda between 1995 and 1999. All contacts were systematically evaluated for active tuberculosis and risk factors for active disease. Among the 1,206 household contacts, 76 secondary cases (6%) of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
5
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 31 publications
10
152
5
11
Order By: Relevance
“…The prevalence of latent TB infection in the present study is higher than in previous surveys 12,13 in Kampala, Uganda where values of 57% and 66% of TST induration ≥10 mm were reported. Kayanja et al 13 postulated that health workers from clinical departments are at greater risk for latent TB infection due to regular contact with infectious cases in the clinics and wards.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The prevalence of latent TB infection in the present study is higher than in previous surveys 12,13 in Kampala, Uganda where values of 57% and 66% of TST induration ≥10 mm were reported. Kayanja et al 13 postulated that health workers from clinical departments are at greater risk for latent TB infection due to regular contact with infectious cases in the clinics and wards.…”
Section: Discussioncontrasting
confidence: 86%
“…In the present study, an induration of < 10 mm was considered negative for latent TB infection (Table 2) because TB infection is endemic in Uganda 12 . Since there is strong evidence that hospital acquired TB infection is an important occupational problem among HCWs in LMICs (2) and the present respondents are expected to join the workforce shortly after graduating, their health is a matter of concern for continued health care delivery to the majority of Ugandans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cross-transmission events may be common in the setting of nosocomial transmission, incarceration, migration/transportation, and occupational exposures. Prior studies have shown that the amount of transmission that occurs in the household may be small (21,22), but other transmission events (e.g., at social events) (23) may be far more likely to occur within geographically defined boundaries than across them. This may also be true of hotspots (e.g., townships in Cape Town, South Africa) (24) that are geographically isolated from low-incidence areas.…”
Section: Fig 2 Proportion Of Tb Transmission Events In Rio Dementioning
confidence: 99%
“…Study design and enrollment procedures have been described in detail elsewhere. 5,7,23 contact study of Mtb infection and TB disease conducted in Kampala, Uganda. Households were ascertained through an individual with culture-positive TB (index case).…”
Section: Methodsmentioning
confidence: 99%